Peningkatan Cinta Keberagaman Budaya Indonesia Melalui Media FLIP -BOOK dan POP-UP Book - Nasution, Ulfa Dwi Rizki; Fadhilah, Vira Putri; Utari, Vovi; Wardini, Wardini; Sitio, Yuliana Indah Sari; Sitorus, Yustika Afritania; Lubis, Nazriani (LPPI UMN AL WASHLIYAH, 2025)
This study aims to enhance children's appreciation of Indonesia's cultural diversity through the use of flip-book and pop-up book media in an orphanage setting. The community service activity was conducted at Febrian Berkat Karunia Orphanage Foundation in Deli Serdang Regency. The implementation consisted of four stages: preparation, socialization, media demonstration, and evaluation through pretest and posttest. The results showed a significant improvement in children’s understanding and appreciation of cultural diversity after engaging with the interactive media. Moreover, the intervention had positive effects on their cognitive, emotional, and fine motor development, as well as in strengthening their cultural identity. Flip-books and pop-up books proved to be effective educational tools that are engaging, interactive, and enriching for children's learning experiences on Indonesian cultural diversity.Keywords: Culture, Flip-book, Pop-up book